2003
DOI: 10.1167/iovs.03-0391
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Isometric Exercise on Subfoveal Choroidal Blood Flow in Smokers and Nonsmokers

Abstract: These data indicate abnormal CBF regulation in chronic smokers compared with age-matched nonsmoking subjects during isometric exercise. The pathways responsible for this abnormal blood flow response remain to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 30 publications
1
36
0
1
Order By: Relevance
“…While a significant change in IOP was observed during the course of isometric exercise, this change dissipated rapidly following completion. These findings are in line with previous studies that observed a significant increase in IOP during isometric exercise, which decreased back to baseline [22][23] or even below baseline within a minute following the exercise [14][15][16][17][18][19]. Movaffafhy et al [14] and Riva et al [15] observed that an increase in blood volume within the large choroidal vessels could explain the increase in IOP during squatting.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…While a significant change in IOP was observed during the course of isometric exercise, this change dissipated rapidly following completion. These findings are in line with previous studies that observed a significant increase in IOP during isometric exercise, which decreased back to baseline [22][23] or even below baseline within a minute following the exercise [14][15][16][17][18][19]. Movaffafhy et al [14] and Riva et al [15] observed that an increase in blood volume within the large choroidal vessels could explain the increase in IOP during squatting.…”
Section: Discussionsupporting
confidence: 91%
“…The effect of exercise on IOP has been well studied [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Although the majority of studies agree that dynamic exercise produces a decrease in IOP [8][9][10][11][12][13], no consensus was found for the effect of isometric exercise (i.e., static strength training where the joint angle and muscle length do not change during the contraction).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of smoking on eye can be summarized as decreased blood flow in ocular and retinal blood vessels, deranged autoregulation, increased vascular resistance in chorioretinal and optic nerve circulation and abnormal choroidal vascular reactivity (Wimpissinger et al 2004). The role of increased oxidative stress and lipid peroxidation and reduced oxygen-carrying capacity of haemoglobin has also been emphasized in smokers.…”
Section: Discussionmentioning
confidence: 99%
“…All subjects reported normal ocular health (with no history of ocular disease, injury or surgery), and no history of any systemic health problems or cardiovascular disease. As previous studies 26 have indicated that choroidal blood flow regulation may be altered in chronic smokers, no regular cigarette smokers were included in the study. All subjects were recruited from the staff and students of our university, and all gave written informed consent to participate.…”
Section: Methodsmentioning
confidence: 99%